The Dignity of Persons Deprived of Their Liberty: An Analysis of Prison Conditions in Brazil - Burbano Herrera, Clara (2025)
This article presents a critical analysis of the current situation of persons deprived of liberty in Brazil, exploring the reasons why prison conditions fail to protect the dignity of these individuals and do not meet international human rights standards. We argue that the deplorable situation in Brazilian prisons is the result of a series of deficiencies on the part of the State, both in terms of negligence in implementing criminal procedural legislation and in criminal policy decisions grounded in social marginalisation and necropolitics. We argue that the inhuman conditions in prisons are the outcome of a deliberate political decision.Our theoretical analysis is based on the work of Achille Mbembe, who asserts that necropolitics is the power exercised by the State, through its institutionalised structures, to determine which bodies are deemed disposable in society, relegating vulnerable groups to death through neglect or active persecution, disguised as institutional actions.